Use of knowledge management systems: analysis of the strategies of Brazilian small and medium enterprises. Issue 2 (20th February 2020) - Marques Júnior, Euro; Gobbo, Jose Alcides; Fukunaga, Fernando; Cerchione, Roberto; Centobelli, Piera
Abstract : Purpose: This paper aims to highlight the degree of diffusion and intensity of use of knowledge management systems (KMSs) among small and medium enterprises (SMEs) in Brazil and apply a taxonomy that synthesizes the strategies of use of KMSs by the SMEs. In addition, it seeks to better understand the processes, practices and technologies of KM by SMEs, pointing improvements in the KMS of Brazilian SMEs and contributing to obtain better results in the search for efficiency and innovation. Design/methodology/approach: Based on a literature review on KMSs used by SMEs, an empirical investigation was conceived, developed and conducted through online questionnaires involving 49 selected SMEs operating in several sectors. Findings: This paper reinforces the results of the previous work of Cerchione and Esposito (2017) that point to the existence of a reciprocal relationship between KM-Tools and KM-Practices: one reinforces the other and vice versa. On the other hand, it indicates a difference in the behavior of Brazilian companies in relation to the sample of Italian companies studied by Cerchione and Esposito (2017), which presented a negative correlation between the general differentiation index and the general use intensity index of SMEs, while the Brazilian ones showed a positive correlation. Research limitations/implications: The study points out the need for greater dissemination of practices and tools to support knowledge management (KM), as well as greater support for the implementation and effective use of these practices and tools within the organizational context of SMEs. Practical implications: This paper identifies the main practices and tools to support KM used by Brazilian SMEs, indicating the need for investments in employee training and acquisition of tools. Social implications: SMEs represent an important part of the generation of jobs and income in Brazil. Initiatives that lead to the successful implementation of tools and practices to support KM can increase the efficiency and productivity of these organizations. Originality/value: This paper applies in a sample of Brazilian companies the taxonomy proposed by Cerchione and Esposito (2017) combining strategies of SMEs for the use of KMSs.